2009
DOI: 10.1161/hypertensionaha.109.139741
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin II Type 1A Receptors in Cardiovascular Reactivity and Neuronal Activation After Aversive Stress in Mice

Abstract: Abstract-We determined whether genetic deficiency of angiotensin II Type 1A (AT 1A ) receptors in mice results in altered neuronal responsiveness and reduced cardiovascular reactivity to stress. Telemetry devices were used to measure mean arterial pressure, heart rate, and activity. Before stress, lower resting mean arterial pressure was recorded in AT 1AϪ/Ϫ (85Ϯ2 mm Hg) than in AT 1A ϩ/ϩ (112Ϯ2 mm Hg) mice; heart rate was not different between groups. Cage-switch stress for 90 minutes elevated blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 34 publications
3
50
1
Order By: Relevance
“…For example, in the CVLM, ANG II and AT 1 Rs mediate depressor and bradycardic responses (2,8,9,27,38), inhibition of the baroreflex (3,32,35,39), stress responses (13,32), and vasopressin release (1). In this report, we showed that microinjections of ANG-(1-12) elicit cardiovascular responses, which are mediated via its conversion to ANG II and ANG-(1-7).…”
Section: Perspectivesmentioning
confidence: 66%
“…For example, in the CVLM, ANG II and AT 1 Rs mediate depressor and bradycardic responses (2,8,9,27,38), inhibition of the baroreflex (3,32,35,39), stress responses (13,32), and vasopressin release (1). In this report, we showed that microinjections of ANG-(1-12) elicit cardiovascular responses, which are mediated via its conversion to ANG II and ANG-(1-7).…”
Section: Perspectivesmentioning
confidence: 66%
“…Further investigations have found that NO,45 IL‐6,25 and corticotrophin‐releasing hormone and activation of the hypothalamic‐pituitary‐adrenal axis46 are directly involved in the physiological responses to CSS. The renin‐angiotensin system plays a complex role in the pressor response to CSS, with AT 1A receptors having both prohypertensive and antihypertensive roles, depending on their location 3, 33, 34, 47, 48, 49. Future research is needed to determine whether endothelium‐derived ET‐1 interacts with these other pathways or vice versa to mediate the acute pressor response.…”
Section: Discussionmentioning
confidence: 99%
“…ANG II exerts its sympathoexcitatory and pressor effects by activating AT 1 Rs, increasing NADPH oxidase-mediated production of ROS leading to ROS-mediated inhibition of delayed rectifier potassium channels and increased neuronal firing rate (14,15). Besides their effect on neuronal activity, ROS also upregulate MIF in PVN neurons (27).…”
Section: Discussionmentioning
confidence: 99%
“…The paraventricular nucleus of the hypothalamus (PVN) plays a central role in integrating the physiological response to stress, and angiotensin II (ANG II) signaling within the PVN has been shown to contribute to both the activation of the hypothalamic-pituitary-adrenal (HPA) axis and elevations in blood pressure and heart rate during stress (1,6,14,31,51). Previous work from our laboratory demonstrated that within the brain macrophage migration inhibitory factor (MIF) is an important intracellular counterregulator of ANG II in PVN neurons and that this action is mediated by the intrinsic thiol-protein oxidoreductase (TPOR) activity that is exerted by a C-A-L-C motif at residues 57-60 of MIF (40,57,58).…”
Section: Exaggerated Activation Of the Sympathetic Nervous System Andmentioning
confidence: 99%
See 1 more Smart Citation